2008
DOI: 10.1103/physrevb.77.134432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of current on nanoscale ring-shaped magnetic tunnel junctions

Abstract: We report the observation and micromagnetic analysis of current-driven magnetization switching in nanoscale ring-shaped magnetic tunnel junctions. When the electric current density exceeds a critical value of the order of $6\times 10^{6}$A/cm$^2$, the magnetization of the two magnetic rings can be switched back and forth between parallel and antiparallel onion states. Theoretical analysis and micromagnetic simulation show that the dominant mechanism for the observed current-driven switching is the spin torque … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…A TMR ratio of 100% has been used in the calculation of resistance in Figure 4, which is similar to the ratios currently used in commercial MRAM [37]. Such a treatment for the calculation of the resistance of magnetic tunnel junctions has been shown to compare well to experimental data in ring shaped MTJs and MTJs using artificial ferrimagnets [38,39]. Theoretical calculation of the resistance of GMR structures with multiple states was also shown in the work by Zhang and Levy [34].…”
Section: A Operation Of Chiralmem Multi-bit Magnetic Memorymentioning
confidence: 69%
“…A TMR ratio of 100% has been used in the calculation of resistance in Figure 4, which is similar to the ratios currently used in commercial MRAM [37]. Such a treatment for the calculation of the resistance of magnetic tunnel junctions has been shown to compare well to experimental data in ring shaped MTJs and MTJs using artificial ferrimagnets [38,39]. Theoretical calculation of the resistance of GMR structures with multiple states was also shown in the work by Zhang and Levy [34].…”
Section: A Operation Of Chiralmem Multi-bit Magnetic Memorymentioning
confidence: 69%
“…We consider a typical asymmetric nanoring MTJ which consists of a sandwiched three-layer structure: Co 60 Fe 20 B 20 (3 nm)/ AlO x (0.6 nm)/Co 60 Fe 20 B 20 (2.5 nm) [6,7], which is realistic but schematically shown in Fig. 1(a).…”
Section: Model System and Computationmentioning
confidence: 99%
“…Previous experiments and micromagnetic simulations indicated that in ferromagnetic rings of micrometer size the current induced circular Amp ere field is the dominant mechanism for switching the vortex states [9], while in those with diameters of less than 100 nm the spin-transfer torque effect predominates in reversal of the onion state [6]. Here we have chosen to investigate nanorings with outer diameter of 200 nm, which were experimentally well studied by Wei et al [7].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations